Kajian Penggunaan Teknologi Pengesanan Kemalangan bagi Pengurusan Keselamatan di Tapak Bina - Wan Mahamud, Wan Nursyazwana; Kasim, Narimah; Zainal, Rozlin; Shareh Musa, Sharifah Meryam; Mohd Noh, Hamidun (Research in Management of Technology and Business, 2021)
The construction industry sector is an increasingly challenging sector with construction project activities that can be categorized as dangerous. Use of accident detection technology for safety management on construction sites. This technology will be able to reduce or anticipate accidents that occur during construction work. Therefore, this study was conducted to examine the types and advantages of technology, as well as barriers to the use of accident detection technology for safety management on construction sites. To achieve these objectives, this study will use quantitative methods through questionnaires to collect data for this study. The respondents of this study consisted of Grade 7 contractors registered in the state of Kuala Terengganu and involved project managers and security managers who are experienced in the field of the construction industry. The data to be collected will be analyzed using SPSS software. As a result of the data analysis that has been done, it is found that different types of information and communication technology are used to collect data quickly and accurately for security management on construction sites. Meanwhile, the advantages of accident detection technology can increase the safety of the construction site is an advantage supported by the respondents. However, barriers to accident detection technology require high costs which are barriers supported by respondents to ensure safety at the construction site. Therefore, the objectives of this study will be achieved and the results of this study can provide effective information to contractors so that safety at the construction site is more guaranteed without accidents. In conclusion, the parties involved should work together to ensure that the use of accident detection technology for safety management at construction sites can be expanded for use in the construction industry.